Histoplasmosis laryngeal: report first case in Colombia - Moriones Robayo, Carlos Alberto (Universidad del Valle, 2014)

(untitled) (Colomb Med (Cali))
Laryngeal histoplasmosis is a fungal infection that is frequent in Colombia. Laryngeal histoplasmosis usually occurs in immunocompromised patients through the dissemination of the fungus from the lungs to other organs. Histoplasmosis isolated laryngeal (primary) is rare. If a patient presents with a history of immunosuppression by renal transplant, primary laryngeal histoplasmosis with supraglottic granulomatous inflammation that was treated with amphotericin B and Itraconazole, with complete resolution of laryngeal lesions.